MEDICAL STUDENT’S KNOWLEDGE, ATTITUDES AND PERCEIVED BARRIERS TOWARDS RESEARCH: A STUDY AMONG NEPALESE STUDENTS - Paudel, Sudarshan; B, Krishna; Acharya, Balakrishnan M (International Journal of Research -GRANTHAALAYAH, 2019)
Background: Undergraduate research exposure leads to academically dexterous and professionally unbeaten physicians. Undergraduate medical courses have research curriculum in Nepal but little is known about how students perceive research. The aim of this survey was to assess the knowledge, attitudes and perceived barriers towards research among medical students at Patan Academy of Health Sciences Nepal. Method: A cross-sectional survey based on a questionnaire applied to 253 undergraduate medical students from year two to six enrolled in Patan Academy of Health Sciences, Nepal. Results: The response rate was 97 %. Majority respondents (78.3%) have viewed that medical curriculum demands sincere dedication and effort at the cost of research funding (71.5%), allocated time for research (61.7%), well-equipped laboratory and technologies. Besides that, ethical approval (47.8%), administrative approval (46.6%) and supportive staff (41.1%) are other barricade to research. Conclusion: The students have positive perception and attitude towards research. They have faced some barriers thus college needs to train students in research and provide supervision in a small research project. This model would improve academic learning, skills acquisition, encourage student interest in research, reduce barriers to student research and make better use of limited resources.